Homomorphic Encryption Security For Cloud Computing (Global Journal of Computer Science and Technology, 2019)
As the Data and Technology is increasing day by day the security and privacy issues are becoming a major concern now a days, with the advent of different security mechanisms there are some bottlenecks. In this work we are giving the essence and importance of an encryption scheme called homomorphic encryption and its related issues.
Keywords: encryption; homomorphic encryption; RSA; security